Logistics sprawl and the change in freight transport activity: A comparison of three measurement methodologies. (May 2022) - Trent, Nadia M.; Joubert, Johan W.
Abstract: Logistics sprawl has been observed in many urban areas around the world, but the assumed link between increased logistics sprawl and increased freight transport activity has little empirical evidence. Because this link could influence policy-making to either fight or facilitate logistics sprawl, this paper investigates the implications of using different methodologies to quantify the relationship. Three different methodologies are compared. The first two methodologies are from well-respected sources in literature and the third is proposed in this paper. The methodologies measure transport activity related to logistics sprawl in three urban areas in South Africa between 2010 and 2014. The results from the methodologies are contradicting with the methodology proposed in this paper questioning the link between logistics sprawl and freight transport activity altogether. The comparison of the methodologies also shows that it is essential to include empirical data of actual vehicle movement when investigating logistics sprawl's impact on transport activity.